2019
DOI: 10.1371/journal.pone.0222273
|View full text |Cite
|
Sign up to set email alerts
|

DNA analysis of elasmobranch products originating from Bangladesh reveals unregulated elasmobranch fishery and trade on species of global conservation concern

Abstract: Trade involving elasmobranch products in Bangladesh is a four-decade-long practice in large scale and there is little understanding of its impact on species composition, population, and subsequent conservation. Capacity for monitoring and identification is lacking in landing and shark processing centres. A rapid survey and collection of tissue samples were performed in three landings and nine shark processing centres between 2016 and 2017 in the south-eastern coastal region of Bangladesh. Sequencing for a 707-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Within the devil ray distribution range, the Bay of Bengal offers high nutrient content, high biological productivity and oceanographic mixing, owing to upwelling, providing an ideal habitat for the predominantly pelagic planktivorous filter feeders such as devil rays (Somayajulu, Murty & Sarma, 2003; Smith et al, 2008; Adnet et al, 2012; Amaral et al, 2017). Two devil ray species have been reported within the Bangladesh region of the Bay, namely M. mobular (including former M. diabolus and M. japanica ) and M. kuhlii (Hoq, Haroon, & Hussain, 2011; Haque, Biswas & Latifa, 2018; Haque, Das & Biswas, 2019); M. hypostoma was also reported (presumably misidentified as this species only occurs in the Atlantic Ocean). Of these ray species, only M. mobular is protected in Bangladesh – under Schedule II of the Wildlife (Conservation and Security) Act, 2012 that protects 29 elasmobranch species under two schedules.…”
Section: Introductionmentioning
confidence: 99%
“…Within the devil ray distribution range, the Bay of Bengal offers high nutrient content, high biological productivity and oceanographic mixing, owing to upwelling, providing an ideal habitat for the predominantly pelagic planktivorous filter feeders such as devil rays (Somayajulu, Murty & Sarma, 2003; Smith et al, 2008; Adnet et al, 2012; Amaral et al, 2017). Two devil ray species have been reported within the Bangladesh region of the Bay, namely M. mobular (including former M. diabolus and M. japanica ) and M. kuhlii (Hoq, Haroon, & Hussain, 2011; Haque, Biswas & Latifa, 2018; Haque, Das & Biswas, 2019); M. hypostoma was also reported (presumably misidentified as this species only occurs in the Atlantic Ocean). Of these ray species, only M. mobular is protected in Bangladesh – under Schedule II of the Wildlife (Conservation and Security) Act, 2012 that protects 29 elasmobranch species under two schedules.…”
Section: Introductionmentioning
confidence: 99%
“…Before the field studies, an annotated checklist of all elasmobranchs reported from Bangladeshi waters was prepared from published documents found through a literature review [ 27 , 34 – 36 , 71 – 73 , 77 – 89 ].…”
Section: Methodsmentioning
confidence: 99%
“…Limited knowledge of elasmobranch diversity and their particular threats, habitat use, catch and bycatch trend, is leading to depletion of several species with global conservation concern in the Bay of Bengal region (e.g. Ganges shark, giant guitarfish, and wedgefish, sawfish amongst many) [ 13 , 24 , 27 , 28 ]. In addition, a historical baseline is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty in correctly identifying cartilaginous fish is due to the fact that they arrive either already in processed state in markets, or only their fins are landed, making morphological identification impossible (VOOREN & KLIPPEL, 2006). Because of this, molecular markers have been widely applied to identify species exhibiting economic interest (WARD et al, 2005;KYLE & WILSON, 2007;SEVILLA et al, 2007;HOLMES et al, 2009;ASIS et al, 2014;BINEESH et al, 2015;FIELDS et al, 2015;SEMBIRING et al, 2015;VAN DER MERWE & GLEDHILL, 2015;CHUANG et al, 2016;STEINKE et al, 2017;ALMERÓN-SOUZA et al, 2018;FEITOSA et al, 2018;FERRETE et al, 2019;HAQUE et al, 2019;HELLBERG et al, 2019;MUTTAQIN et al, 2019;RODRIGUES-FILHO et al, 2020).…”
Section: Molecular Identificationmentioning
confidence: 99%
“…In this context, molecular methodologies, such as DNA Barcoding, may be applied to correctly identify different species, as they allow for better accuracy in elasmobranch identification (WARD et al, 2005, HOLMES et al, 2009ASIS et al, 2014;BINEESH et al, 2017;FIELDS et al, 2015;SEMBIRING et al, 2015;VAN DER MERWE & GLEDHILL, 2015;CHUANG et al, 2016;STEINKE et al, 2017;ALMERÓN-SOUZA et al, 2018;FEITOSA et al, 2018;FERRETE et al, 2019;HAQUE et al, 2019;HELLBERG et al, 2019;MUTTAQIN et al, 2019;RODRIGUES-FILHO et al, 2020). Thus, the DNA Barcode technique serves as a basic tool in the implementation of shark and ray management plans aiming at conservation actions.…”
Section: Introdutionmentioning
confidence: 99%